Case and Adverbials in Inari Saami and Finnish - Nelson, Diane (Nordlyd, 2004)
This paper explores the relationship between case-marked adverbials and event structure in two related languages, Inari Saami and Finnish. New data is presented to show that while oblique case-marked adverbials do not delimit events in either language, the two languages diverge with respect to accusuative adverbials. Finnish shows a one-to-one mapping between case and event delimitation, while in Inari Saami not all accusative adverbials delimit events. These findings lend support to proposals by Arad (1998) and Tenny (1987) that each predicate may contain only one event delimiter.